The Role of Non-Governmental Organisations (NGOs) on the Socio¬economic Transformation of Rural Areas in Nyarusiza Sub-County Kisoro District. - Izabayo, Joan (Kabale University, 2023)
The findings of the study research focused on the role of non-governmental organizations NGOs) and the socio-economic transformation of rural areas in Nyarusiza Sub-county Kisoro strict. The study's objectives were to discover the services provided by non-governmental organizations (NGOs) to society in the Nyarusiza sub-county Kisoro district, to determine the effect of NGOs on increased rural incomes in the Nyarusiza sub-county Kisoro district, and to investigate the challenges faced by NGOs in the transformation of rural areas in Nyarusiza sub-county Kisoro district. In chapter two, there was a critical review of the issues that have been explored and studied both theoretically and empirically in the existing literature on non-governmental organizations as an independent variable and the socio-economic transformation of rural areas as a dependent variable. The data collection methods are put into action in Chapter 3. The research used both qualitative and quantitative methods of data collection and analysis. The research used simple random sampling techniques in collecting and analyzing data, which were used to provide equal chances for the sample size. Purposive sampling was also used to collect data from respondents who participated in the study. The findings of the study obtained from the field were analyzed and interpreted in chapter four, and a summary of the findings was presented in chapter five. The study concludes that the NGOs in the Nyarusiza sub-county, Kisoro district, like to manifest themselves as advocates of social change. The priority for achieving effective social change is to eliminate all forms of discrimination in society, and the empowerment of women is the first step. No doubt, the poorest women are the most disadvantaged section of society, especially because they do not have access to information and resources. So they are lagging in the process of development. NGOs would like to involve these women and enhance their participation in the development process, and the study also recommends that NGOs work together with their government counterparts and have done tremendous work. Many NGOs have not only grown in size but have also developed infrastructures for research, training, and demonstration of alternative methods· for increasing rural income. There are several successful non-governmental organizations (NGOs) that have actively participated in the development of society by creating employment opportunities and livelihoods for the poor section of society through non-governmental organizations (NGO's) and the socio-economic transformation of rural areas in Nyarusiza Sub-county Kisoro district.